Um diálogo com os discursos dos educadores, do Sesc São Carlos: vozes e sentidos de uma prática pedagógica - Motta, Priscila Canova (2020)
Our aim with this research is to discuss issues related to education and especially to non-formal education based on the discursive manifestations of the educators of the Sesc São Carlos Children and Youth Sector Programs. We propose to carry out a dialogue with the speeches of seven educators from the Curumim Programs, Espaço de Brincar e Juventudes from the Childhood and Youth sector of Sesc São Carlos and analyze the statements of the discursive manifestations of these educators and the ways of producing meaning about being an educator and their pedagogical practices in the context of non-formal education. We chose to carry out this research with the theoretical framework of the Circle of Bakhtin. We also held a conversation with the theoretical framework of some researchers on education, such as Paulo Freire, Moacyr Gadotti and Rubem Alves and on non-formal education from some researchers and scholars in the area (COOMBS, TRILLA, CARNOY, DANTAS, GARCIA, GHANEM, GOHN, TORRES, NOGUEIRA, PARK) to better understand the experience of Sesc SP's Childhood and Youth Sector Programs.